Costos de la Detección Oportuna de Cáncer de Mama en Población Femenina del Cantón Machala - Aguilar Sanmartín, Nicole Stefany (My University, 2025)
Breast cancer is one of the leading causes of female mortality in Ecuador, and in Machala this problem is worsened by barriers to access, technological limitations, and the absence of systematic prevention programs. To address this, the costs of implementing an early detection program for women aged 40 to 49 years a population of 21,437 were evaluated, projecting 80% coverage over three years. Using a quantitative and health economics approach, the estimated total cost was $2,626,892.50 (an average of $153.22 per patient) to benefit 17,150 women, revealing a critical deficit in public infrastructure and the need for strategic partnerships with institutions such as SOLCA Machala and private providers. The results show that the program is technically and economically feasible, as investment in early screening reduces advanced treatment costs and improves survival rates. Its success will depend on effective inter-institutional coordination, strengthening of primary care, and community involvement, making it replicable in similar localities and a key strategy for promoting health equity.
El cáncer de mama constituye una de las principales causas de mortalidad femenina en Ecuador y, en Machala, esta situación se agrava por barreras de acceso, limitaciones tecnológicas y ausencia de programas preventivos sistemáticos; por ello, se evaluaron los costos de implementar un programa de detección oportuna en mujeres de 40 a 49 años, población de 21.437 personas, proyectando una cobertura del 80% en tres años. Con un enfoque cuantitativo y económico en salud, se estimó un costo total de $2,626,892.50 (promedio de $153.22 por paciente) para beneficiar a 17.150 mujeres, evidenciándose un déficit de infraestructura pública y la necesidad de alianzas con instituciones como SOLCA Machala y prestadores privados. Los resultados demuestran que el programa es técnica y económicamente viable, ya que invertir en tamizaje temprano reduce costos de tratamientos avanzados y mejora la supervivencia, siendo clave la coordinación interinstitucional, el fortalecimiento del primer nivel de atención y la participación comunitaria, lo que lo hace replicable en otras localidades similares y esencial para promover la equidad en salud.
Keywords: CÁNCER DE MAMA; DETECCIÓN OPORTUNA; COSTOS EN SALUD; TAMIZAJE